The derivation of a dynamical model for a manta robot and its control - Ikeda, Masaaki; Hikasa, S; Watanabe, K; Nagai, I (2015)
In this paper, we derive a dynamical model for a manta robot by taking account of a pectoRAL-fin propulsion mechanisms. Especially, the model is derived by considering the force generated from such a specialized propulsion mechanism, together with estimating added masses and moment due to a cubic body form used in this research. The effectivesness of the dynamical model is verified by comparing the simulation results based on the model with the measurement values using an actual robot.